2004
DOI: 10.1007/bf03190588
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling of pharmacokinetic parameters in drug discovery: Can human CL, Vss and t1/2 be predicted fromin-vivo rat data?

Abstract: In a drug discovery environment, reasonable go/no-go human in-vivo pharmacokinetic (PK) decisions must be made in a timely manner with a minimum amount of animal in-vivo or in-vitro data. We have investigated the accuracy of the in-vivo correlation between rat and human for the prediction of the total systemic clearance (CL), the volume of distribution at steady state (Vss), and the half-life (t1/2) using simple allometric scaling techniques. We have shown, using a large diverse set of drugs, that a fixed expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 46 publications
4
109
1
Order By: Relevance
“…Although qualitative and quantitative in vitro/in vivo correlation analysis based on data generated using human liver tissues and recombinant enzymes has been applied successfully to many drugs that are cleared by P450-dependent metabolism, these approaches have proven less definitive for glucuronidated compounds, mainly for the reasons alluded to earlier (Soars et al, 2003;Miners et al, 2004;Kilford et al, 2009). In addition, allometric scaling based on in vivo preclinical models has been successful for P450-eliminated drugs, provided that species-specific P450 enzymes have been well studied and understood (Caldwell et al, 2004;De Buck et al, 2007). On the other hand, given the current challenge of using preclinical species to predict human pharmacokinetics for predominantly glucuronidated compounds, more research is required to fully understand species differences and substrate specificity of UGT enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Although qualitative and quantitative in vitro/in vivo correlation analysis based on data generated using human liver tissues and recombinant enzymes has been applied successfully to many drugs that are cleared by P450-dependent metabolism, these approaches have proven less definitive for glucuronidated compounds, mainly for the reasons alluded to earlier (Soars et al, 2003;Miners et al, 2004;Kilford et al, 2009). In addition, allometric scaling based on in vivo preclinical models has been successful for P450-eliminated drugs, provided that species-specific P450 enzymes have been well studied and understood (Caldwell et al, 2004;De Buck et al, 2007). On the other hand, given the current challenge of using preclinical species to predict human pharmacokinetics for predominantly glucuronidated compounds, more research is required to fully understand species differences and substrate specificity of UGT enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In one example, it was determined that simple allometry can accurately predict the elimination rate-constant for irbesartan from animal data (Kumar and Srinivas, 2008). In another study, it was concluded that human half-life values can adequately be predicted from rat half-life values using either linear regression or allometric scaling between human and rat (Caldwell et al, 2004). About 76% and 77% of the values were predicted within an average fold error of less than 3 for the regression and allometric method, respectively.…”
Section: Predicting Half-lifementioning
confidence: 99%
“…When a 10-fold factor is applied to take into account the allometric and pharmacokinetic differences between humans and rats (Caldwell et al, 2004), these doses would translate to oral doses in rats of 10-13 mg/kg for lisdexamfetamine dimesylate, 3.0-5.0 mg/kg for methylphenidate hydrochloride and 100-150 mg/kg for modafinil, which are similar to those employed in this experimental study.…”
Section: Drugs and Selection Of Dosesmentioning
confidence: 99%